Treatment of automotive industrial wastewater utilizing Canna x Generalis in a simulated vertical flow constructed wetland - Antonio, Heidi T.
In the Philippines, DENR has mandated the regulation of oil and grease, COD, and TSS for automotive parts manufactures. Wastewaters from industries have varying pollution strength that requires efficient treatment systems of combined physical, biological, and chemical processes. However, these methods tend to be labor intensive and costly. Constructed wetlands have become a popular treatment method for industrial wastewater because of its simplicity requiring less technical expertise compared to other technologies. In this study, four vertical subsurface flow constructed wetlands composed of cylindrical drums with diameter of 30 cm and height of 90 cm were designed to treat industrial wastewater in parallel experiments. The four constructed wetland units had various set-ups (with & without Canna X Genera/is, with & without zeolite, with & without air vent) to determine the effect of the treatment efficiency. Water quality samples were collected from each unit, and were analyzed for pH, ORP, TSS, COD, aluminum, oil and grease. The influent characteristics of COD=10,480 mg/L and TSS=1198.9 mg/L were parameters being evaluated in terms of removal efficiency. According to the findings, constructed wetland with plants, zeolite and air vent demonstrated higher removal efficiency in comparison to constructed wetlands without these features. The removal efficiencies registered 93.35% and 90.67% for COD and TSS, respectively.